2021
DOI: 10.1016/j.celrep.2021.109694
|View full text |Cite
|
Sign up to set email alerts
|

The prolyl-isomerase PIN1 is essential for nuclear Lamin-B structure and function and protects heterochromatin under mechanical stress

Abstract: Highlights d PIN1 stabilizes HP1a in complex with LaminB in a phosphorylation-dependent manner d PIN1 function maintains nuclear envelope structure under mechanical stress d PIN1 loss causes HP1a degradation, heterochromatin relaxation, transposon derepression d Loss of PIN1 nucleo-protective function contributes to Alzheimer's disease

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 100 publications
1
6
0
Order By: Relevance
“…Unravelling the mechanism of PIN1 complex formation with L1 ORF1p may reveal novel therapeutic avenues. Recently, Napoletano et al have demonstrated the role of PIN1 in the negative regulation of transposable elements including L1 transcripts in neurons during ageing or mechanical stress as PIN1 is essential for nuclear envelope integrity and heterochromatin maintenance [ 61 ]. However, in spite of high PIN1 expression in cancer cells, L1 expression is also upregulated, indicating dysregulation of other L1 regulatory mechanisms independent of PIN1 or reduced PIN1 nuclear activity in the presence of L1 ORF1.…”
Section: Discussionmentioning
confidence: 99%
“…Unravelling the mechanism of PIN1 complex formation with L1 ORF1p may reveal novel therapeutic avenues. Recently, Napoletano et al have demonstrated the role of PIN1 in the negative regulation of transposable elements including L1 transcripts in neurons during ageing or mechanical stress as PIN1 is essential for nuclear envelope integrity and heterochromatin maintenance [ 61 ]. However, in spite of high PIN1 expression in cancer cells, L1 expression is also upregulated, indicating dysregulation of other L1 regulatory mechanisms independent of PIN1 or reduced PIN1 nuclear activity in the presence of L1 ORF1.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation analysis of epigenetic terms showed a positive correlation only with proAD, as expected, whereas a negative correlation and no regulation were observed in the posAD and defAD stages, respectively. The Tau-dependent alteration of chromatin remodelling pathways associated with the proAD stage indicates an early modification of chromatin structures (Eissenberg and Elgin, 2014; El Hajjar et al, 2019; Frost et al, 2014; Napoletano et al, 2021). The reductions in the levels of heterochromatin markers, HP1α and H3K9me3, in the proAD-mimic model indicated Tau as a major factor leading to the loss of heterochromatin.…”
Section: Discussionmentioning
confidence: 99%
“…A study using HCMV-infected fibroblasts showed that Pin1 binds to pSer22-Pro of lamin A and promotes the disintegration of the nuclear membrane by modulating the conformation of lamin [ 33 ]. Furthermore, it has been reported that Pin1 is essential for the maintenance of the structure of nuclear B-type lamin and the anchoring function of heterochromatin protein 1α, playing a role in preventing alterations in the nuclear membrane and relaxation of the heterochromatin [ 34 ]. Based on these reports, we speculated that Pin1 binds to phosphorylated lamins and induces and promotes the disruption of the nuclear membrane in mouse oocytes.…”
Section: Discussionmentioning
confidence: 99%